if x = -2 and y = -1 are the solutions so find the value of p in 5x + 2py = 2p

Since x=-2 and y =-1 are the solution of the equation, put the value of x and y to get:

5(-2) + 2p(-1) = 2p

-10 - 2p = 2p

-10 = 2p + 2p

4p = -10

p = -10/ 4

p = -5/2

**
**

if x = -2 and y = -1 are the solutions so find the value of p in 5x + 2py = 2p

Since x=-2 and y =-1 are the solution of the equation, put the value of x and y to get:

5(-2) + 2p(-1) = 2p

-10 - 2p = 2p

-10 = 2p + 2p

4p = -10

p = -10/ 4

p = -5/2

**
**

What are you looking for?